Mercy Watson to the rescue / Kate DiCamillo ; illustrated by Chris van Dusen. - DiCamillo, Kate.; Van Dusen, Chris (Cambridge, MA : Candlewick Press, 2005)
After Mercy the pig snuggles to sleep with the Watsons, all three awaken with the bed teetering on the edge of a big hole in the floor.
Keywords: Swine -- Fiction; Neighbors -- Fiction; Fire departments -- Fiction; Humorous stories